Numerical investigation of composite materials reinforced with carbon nanotubes wav - Farsadi, Morteza (2010)
Regarding thermal, mechanical and electrical properties, substantial prospective advances have been offered by Nanotube-reinforced polymers in comparison with pure polymers. This project studies the extent to which the effective stiffness of these materials can be influenced by the characteristic waviness of nanotubes embedded in polymers. In order to numerically determine how the mechanical properties of composite materials which are reinforced with carbon nanotube, are affected by nanotube waviness, a 3D element model of sinusoidal is applied. According to the obtained results, nanotube waviness causes a decrease in the effective modulus of the composite compared to the straight nanotube reinforcement. The degree to which this decrease happens depends on the ratio of the sinusoidal wavelength to the nanotube diameter. It is indicated from these results that nanotube waviness can be another mechanism which limits the modulus improvement of nanotube-reinforced polymers. Several different meshes have been applied on the model in order to predict its effect on the mechanical properties of composite. The results show that finding a proper mesh has significant role in evaluating the model.